2022
DOI: 10.1159/000521425
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown and Consumption Patterns among Substance Use Disorder Outpatients: A Multicentre Study

Abstract: <b><i>Introduction:</i></b> COVID-19 has had a great impact on mental health in the general population. However, few studies have focused on patients with substance use disorders (SUDs). This research aimed to compare the clinical status and substance use patterns of SUD outpatients, before and during confinement due to the COVID-19 pandemic. <b><i>Methods:</i></b> This multicentre study recruited 588 patients (29.2% women; M age = 47.4 ± 11.7 years) in thirteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
4
14
0
1
Order By: Relevance
“…In contrast, Schmits ( 27 ) reported an increase in anxiety and depression ( N = 2871 adults, 79.0% females) but without any gender effect. Finally, three studies were in line with these results by showing an increase in substance consumption and psychological distress but without any gender effect ( 28 30 ).…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, Schmits ( 27 ) reported an increase in anxiety and depression ( N = 2871 adults, 79.0% females) but without any gender effect. Finally, three studies were in line with these results by showing an increase in substance consumption and psychological distress but without any gender effect ( 28 30 ).…”
Section: Discussionsupporting
confidence: 66%
“…Not all the PUD had access to residential services or access to housing, food and hygiene, issues that were one of the main concerns of the HR professionals during the pandemic [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown how the pandemic has resulted in changes in the treatment demands placed on addiction centers and the healthcare provision patterns of clinicians [ 25 , 26 , 27 , 44 ], along with the associated impact on patients [ 35 , 36 , 37 , 38 ]. Unlike previous studies, this study focused exclusively on patients with dual pathology and analyzed the evolution of treatment admissions, profiles, and care indicators corresponding to the periods before, during, and after confinement, when various anti-COVID-19 measures were implemented in addiction and mental health services.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the closure of some addiction centers [ 34 ] and the shift to virtual treatment have posed a major challenge to meeting the therapeutic needs of these patients. Therefore, some authors have warned of the worsening of comorbid mental disorders and disruptive behaviors both in confinement periods [ 35 , 36 , 37 ] and in the subsequent periods [ 38 ], in addition to a likely increase in relapses [ 39 ].…”
Section: Introductionmentioning
confidence: 99%